Chaco Canyon - Vivian, R. Gwinn (Digging for the past., 2002)
Relates the nineteenth-century discovery of cliff dwellings in the Chaco Canyon of northwest New Mexico, the excavations of the ancient ruins, and what the artifacts reveal about the civilization of the ancient Pueblo Indians.